2022
DOI: 10.1177/03000605221081662
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting balloon (DEB) versus plain old balloon angioplasty (POBA) in the treatment of failing dialysis access: A prospective randomized trial

Abstract: Objective To compare the efficacy of angioplasty using drug-eluting balloons (DEB) compared with plain old balloon angioplasty (POBA) to reduce the rate of restenosis. Methods This prospective, single-centre, single-blinded, 1:1 randomized, clinical trial enrolled patients that had primary or restenotic lesions in native upper extremity arteriovenous (AV) fistulas or at the graft-venous anastomosis. Patients were randomized to angioplasty with a POBA or a DEB. The primary effectiveness endpoints were freedom f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(226 reference statements)
0
8
0
Order By: Relevance
“…Eighty‐five articles were retained after title/abstract curation (excluding 433 records). Thereafter, we read the full text and analyzed 15 RCTs 9,10,13–25 involving a total of 1525 patients for quantitative synthesis (Supporting Information: Figure ). The main characteristics of the included RCTs (country, design, sample size, age, intervention, follow‐up, and main results) are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighty‐five articles were retained after title/abstract curation (excluding 433 records). Thereafter, we read the full text and analyzed 15 RCTs 9,10,13–25 involving a total of 1525 patients for quantitative synthesis (Supporting Information: Figure ). The main characteristics of the included RCTs (country, design, sample size, age, intervention, follow‐up, and main results) are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Pooled analysis of 14 studies 9,10,14–25 ( n = 1489) using a forest plot demonstrated that the primary patency rate in the DCB group ( n = 750) was higher than that in the CB group ( n = 739) at 6 months after balloon expansion (OR = 2.31, 95% CI: 1.69, 3.15, p < .01, Supporting Information: Figure ). No significant heterogeneity was observed ( I 2 = 32.90%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pooled analysis of 14 studies 9,10,[17][18][19][20][21][22][23][24][25][26][27][28] (n = 1489) demonstrated that the forest plot of the 6-month primary patency rate in the DCB group (n = 750) was higher than that in the CB group (n = 739) at 6 months after balloon expansion (OR = 2.31, 95% CI: 1.69, 3.15, P < 0.01, Supplementary Figure S3). No signi cant heterogeneity was observed (I 2 = 32.90%).…”
Section: Primary Patency Rate Of the Target Lesionmentioning
confidence: 99%